Phase formation and characterization of BaBi2Ta2O9 obtained by mixed oxide procedure - da Costa, GCC; Simoes, A. Z.; Ries, A.; Foschini, C. R.; Zaghete, M. A.; Varela, José Arana [UNESP] (Elsevier B.V., 2004)
Ferroelectric layefed-perovskite BaBi2Ta2O9 (BBT) has been prepared successfully by solid-state reaction. The influence of pressure and temperature/time annealing regime on the BBT phase formation was analyzed. The powders were characterized by thermal analysis and Xray diffraction and the sintered pellets by scanning electron microscopy. The crystalline BBT phase, free of secondary phases was obtained at 950 degreesC for 2 h. For an applied field strength of 380 kV/cm, a remnant polarization of 7.6 muC/cm(2) and an electric coercive field of 45.7 kV/cm were obtained. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium bismuth tantalate; perovskite; aurivillius; ferroelectric